Penerapan Flash Card berbasis Gamifikasi dengan Model Pembelajaran Think Aloud Pair Problem Solving untuk Meningkatkan Kemampuan Komunikasi Matematika Siswa tingkat SMP Kelas VII - Sitanggang, Frima; Wardani, Agustria; Piolet, Ika; Dolly, Michael; Saragih, Rini Meilani; Siregar, Nurhasanah (Griya Journal of Mathematics Education and Application, 2025)
Mathematical communication, which involves the ability to express and understand mathematical ideas, is very important in learning. However, many conventional learning methods are less effective in improving these abilities. This study combines gamification-based flash card innovation with the TAPPS model to maximize social and cognitive interactions in mathematics learning, which is expected to have a positive impact on student engagement and understanding. This study aims to explore the application of gamification-based flash cards with the Think Aloud Pair Problem Solving (TAPPS) model to improve junior high school students' mathematical communication skills. The research method used is classroom action research with several cycles that include (Planning, implementation, observation and reflection). Based on the research that has been conducted in 2 cycles with the application of the TAPPS model assisted by gamification-based flash cards, with an average of 84.8% in the first cycle and 94.1% in the second cycle. So there is an increase in students' mathematical communication skills. Therefore, gamification-based flash cards can be used as a medium to improve students' mathematical communication.